Development of IHO S-100 – The new IHO geospatial standard for hydrographic data - Alexander, Lee; Brown, Michael; Greenslade, Barrie; Pharaoh, Anthony (The International Hydrographic Review, 2025)
This manuscript is a reprint of the original paper previously published in 2007 in The International Hydrographic Review (IHR, https://ihr.iho.int/): Alexander, L., Brown, M., Greenslade, B., and Pharaoh, A. (2007). Development of IHO S-100 – The new IHO geospatial standard for hydrographic data. The International Hydrographic Review, 8(1), 56–162. https://journals.lib.unb.ca/index.php/ihr/article/view/20782